Rancang Bangun Sistem Informasi Pencarian dan Penyewaan Rumah Kost di Palangka Raya Berbasis Website - Novianti, Angellita; Nugrahaningsih, Nahumi (Universitas Palangka Raya, 2021)
Information systems are currently growing rapidly which allows all jobs in life to be assisted by information technology. This technology that can help make things easier, faster, safer, and more effective is clearly very useful for anyone who uses it. This includes helping micro, small and medium enterprises (MSME),especially boarding house owners, in promoting their boarding houses and making it easier for someone who is looking for a boarding house to live in. This boarding house search and rental information system is a website-based information system as a means to provide boarding house information for boarding house seekers, as well as for boarding house managers to promote the boarding houses they rent and manage all things related to the boarding house on the website quickly and easy. The methodology used in making this Information System is to use the waterfall method with stages, with stages, namely Requitments Definition depicted by Flowcharts, Requirements Analysis and Definition described by DFD (Data Flow Diagrams), ERD (Entity Relationship Diagrams) and databases. Implementation and Unit Testing with the programming languages used, namely HTML, PHP, CSS, Bootstrap, Javascript and MySQL, Integration and System Testing using the Blackbox Method.